Dopaminergic Modulation of Sensory Attenuation in Parkinson's Disease: Is There an Underlying Modulation of Beta Power? - Macerollo, Antonella; Limousin, Patricia; Korlipara, Prasad; Foltynie, Tom; Edwards, Mark J.; Kilner, James (Frontiers in Neurology, 2019)
Background and aims: Several studies suggest that pathological high amplitude of beta oscillations may cause bradykinesia and other motor symptoms in Parkinson’s disease (PD). Recently, it has been showed that PD patients have abnormality in a neurophysiological phenomenon labelled sensory attenuation. Here, we tested the hypothesis that the abnormality in this mechanism has a causal link with the typical abnormality in beta oscillations in PD. Methods: Sixteen right-handed patients with idiopathic PD and twenty-two age-matched healthy participants were studied. Somatosensory evoked potentials were elicited after electrical stimulation of the median nerve at the wrist. Electrical activity was recorded at the scalp using a 128 channels EEG. Somatosensory evoked potentials were recorded in 2 conditions: at rest and at the onset of movement (a self-paced abduction movement of the right thumb). Results: Healthy participants showed attenuation of the N20- P25 amplitude at movement onset compared to rest condition (P<0.05). PD patients OFF medication showed mild attenuation of the N20-P25 component at movement onset compared to rest condition (P<0.05), whereas they did show greater attenuation of the N20-P25 component at the onset of movement compared to the rest condition when ON medication (P<0.05). There was no evidence for a relationship between the degree of sensory attenuation and the change in beta oscillations. Conclusion: These results confirmed a significant link between dopaminergic modulation and sensory attenuation. However, this study suggest that sensory attenuation and beta oscillations are two independent phenomena.